Sexual morbidity following radical hysterectomy for cervical cancer. Issue 7 (July 2010) - Vrzackova, P; Weiss, P; Cibula, D
Radical hysterectomy for early stage cervical cancer has satisfactory results in terms of survival, but may impact negatively on a patient''s quality of life, which may include sexual dysfunctions. Female sexual dysfunctions (FSD) represent a frequent morbidity but often remain unrecognized and undertreated. Although discussions regarding sexuality are found by many medical doctors to be sensitive and embarrassing, psychosexual counseling is an essential component of comprehensive care for gynecological cancer patients and their partners. The goal of this article is to summarize and discuss available relevant data on FSD in women who have undergone radical hysterectomy for an early stage of cervical cancer.